Literature as History : Autobiography, Testimonio, and the Novel in the Chicano and Latino Experience - García, Mario T. (Book collections on Project MUSE., 2016)
Literature as History represents a unique way to rethink history. Mario T. García, a leader in the field of Chicano history and one of the foremost historian of his generation, explores how Chicano historians can use Chicano and Latino literature as important historical sources.